2023
DOI: 10.3390/pharmaceutics15071992
|View full text |Cite
|
Sign up to set email alerts
|

Colour of Medicines and Children’s Acceptability? A Systematic Literature Review of Children’s Perceptions about Colours of Oral Dosage Forms

Elisa Alessandrini,
Milena Gonakova,
Hannah Batchelor
et al.

Abstract: The colour of a product plays an important role in consumer experiences, and in the context of pharmaceutical products, this could potentially affect a patient’s expectations, behaviours, and adherence. Several studies have been conducted on adults, but little is known about children’s opinions on colours of medicines and to what extent medicines’ colour affects their acceptability. To address this gap, a systematic search in PubMed, Scopus, MEDLINE, and Web of Science was conducted. Two authors independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Mouthfeel was also seen to impact palatability and thus acceptability of particular drug products, highlighting that mouthfeel is not just a function of taste alone. Interestingly, the perceived taste can also be influenced by appearance; one systematic literature review of drug product preferences found an apparent relationship between the color of a drug product and the expected taste, 28 in particular among pediatric patients, 28 though color sensitivity can vary by demographic characteristics, such as age and sex, and cultural characteristics. 24 The variability of findings related to drug product color preference underlines the need for more patient-centered studies that better evaluate the effects of appearance on the acceptability of drug products.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mouthfeel was also seen to impact palatability and thus acceptability of particular drug products, highlighting that mouthfeel is not just a function of taste alone. Interestingly, the perceived taste can also be influenced by appearance; one systematic literature review of drug product preferences found an apparent relationship between the color of a drug product and the expected taste, 28 in particular among pediatric patients, 28 though color sensitivity can vary by demographic characteristics, such as age and sex, and cultural characteristics. 24 The variability of findings related to drug product color preference underlines the need for more patient-centered studies that better evaluate the effects of appearance on the acceptability of drug products.…”
Section: Discussionmentioning
confidence: 99%
“…24 The variability of findings related to drug product color preference underlines the need for more patient-centered studies that better evaluate the effects of appearance on the acceptability of drug products. 28 With regard to the texture, smooth, slippery, and less bitter drug products (ie, those with a coating) were easier to swallow and preferred by patients, though as a lesser priority than size and shape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations